PRIME: A graphical interface for integrating genomic/proteomic databases - Facius, Axel; Englbrecht, Claudia; Birzele, Fabian; Groscurth, Andreas; Schmid, Benjamin; Wanka, Steffi; Mewes, Werner (Proteomics, 2005)
Data mining, finding and integration of information about proteins of interest, is an essential component in modern biological and biomedical research. Even when focusing on a single organism and on only a small number of proteins, there are often dozens of data sources containing relevant information. We are developing PRIME, a protein information environment, to serve as a virtual central database which integrates distributed heterogeneous information about proteins (linked by a common identifier). PRIME has powerful capabilities to visualize all kinds of protein annotation in specialized views. These views can be displayed side by side at the same time and can be synchronized in order to show simultaneously different aspects of identical proteins. These features allow a quick and comprehensive overview of properties of single proteins or protein sets.
Created from Fastlane, Scopus look-up
Keywords: Data mining; Graphical user interface; Integrating distributed information; Retrieval systems; Systems biology